Kepemimpinan Perempuan dalam Jabatan Publik (Studi Kasus pada Kantor Badan Pengawas Pemilu Aceh) - Anggraini, Trisia Diva (Program Studi Ilmu Politik, Universitas Syiah Kuala, Banda Aceh, 2023)
Women's leadership in the context of public office is a topic that attracts attention in an effort to achieve gender equality and women's empowerment. For this reason, it is necessary to realize an increase in women's representation in government institutions and agencies. This study aims to investigate women leaders' strategies in overcoming steorotypes against women's leadership and investigate women's leadership styles in leadership in the Election Supervisory Agency (Bawaslu) office environment in Aceh province, Indonesia. This research uses Gender theory to look at both equality and inequality. As well as the concept of leadership to see how women walk as a leader. This research uses a qualitative approach with a descriptive approach. Data was collected through in-depth interviews with women who served in leadership positions in the Aceh Bawaslu Office, as well as document analysis related to recruitment and promotion policies. The focus of this research is to understand the Strategy of women leaders in overcoming stereotypes of women's leadership in the Aceh Election Supervisory Agency Office. As well as understanding the leadership style of women in the Aceh Election Supervisory Agency Office. The results of this study identified various factors that influence the presence of women in leadership in the Aceh Election Supervisory Agency Office, including persistent gender stereotypes, limited access to resources and opportunities, and social views related to women's roles in the public sphere. However, this study also revealed positive efforts that have been made by the Aceh Bawaslu Office to encourage women's participation in leadership, such as inclusive policies and training opportunities from institutions. The results showed that the strategies carried out included leadership abilities possessed by female leaders by carrying out leadership styles using emotional approaches and family principles. As well as institutionally, women leaders make efforts to increase gender-sensitive critical awareness through their work programs to reduce steorotypes against women.